THE ENIGMA OF KRISHNAMURTI - Maxwell, Patrick (Journal for the study of religion, 1994)
After Krishnamurti left the theosophical world behind in 1929 and embarked on a long career as a solitary teacher, he remained a somewhat enigmatic and controversial figure. This article attempts to explore the elusive character of Krishnamurti's approach, and includes discussions about alleged affinities between Krishnamurti's teaching and the spirit of Zen, his emphasis on direct perception and choiceless awareness, and his attitudes towards 'religion'. The article ends after some observations about the significant following of a man who discouraged followers.